Endocardite a streptococcus bovis e envolvimento do colon - Baptista, SB (2010)
McNeal and Blevins published the first report of Streptococcus bovis infective endocarditis in 1945. In 1951, McCoy suggested, for the first time, that an association could exist between Group D Streptococcus infective endocarditis and colon carcinoma; this association would be demonstrated later (1977) by Klein and unquestionably confirmed by several posterior works. Due to a clinical case of Streptococcus bovis infective endocarditis, which we had the opportunity of diagnosing, a review is made of the existent literature about the association between infection by this agent and the presence of lesions in the colon. Some recommendations are made in what respects the diagnosis and evaluation of patients with Streptococcus bovis infective endocarditis. Finally, the implications and therapeutic strategies in these patients are discussed